Multifunctional MXene/CNT-based layered film for icing detection, anti-icing, and deicing application. Issue 22 (15th November 2022) - Qin, Wenfeng; Lin, Chuanxi; Geng, Junheng; Xue, Yunsheng; Zhong, Mian; Zou, Yao; Liu, Guochun
Abstract: Icing phenomenon usually happens in our daily life, especially in the cold winter or in high altitude areas, which makes us feel inconvenient and greatly threats some fields such as civil aviation or the manufacturing industry. In this study, a multifunctional film with properties of icing detection, anti-icing and deicing was fabricated. One-dimensional material carbon nanotube (CNT) and two-dimensional material Ti3 C2 Tx MXene were combined by two-step vacuum filtration. Polydimethylsiloxane (PDMS) as the flexible hydrophobic materials was then used to encapsulate layered film. Additionally, PDMS curing process on the sandpaper could make the surface of MXene/CNT layered film possess micro-structures. The low surface energy material PDMS and rough surface structures endow MXene/CNT layered film with good water-repellency. Compared with pure PDMS film (103°), the contact angle of MXene/CNT layered film surface reaches 128°. The result exhibits that a waterdrop(100uL) on the layered film surface takes 1425s to be frozen, which takes longer time than glass and pure PDMS. Additionally, excellent sensibility of the layered film could be used to detect icing phenomenon. The result manifests that gauge factor (GF) of MXene/CNT film reaches 15051 so that different icing stages could be identified by layered film clearly. MXene/CNT layered film possesses good electric heating and photo-thermal properties. The result shows that surface temperature can reach 89 °C with the 2.5 V voltage supply, and temperature reaches 95 °C through the radiation of near-infrared lamp as well. The dual-driven heating of MXene/CNT layered film shows the ability of deicing. 1000 mg ice just takes 223s to be melted entirely by 2.5 V input voltage, and 269s by radiation of 200 mW/cm 2, respectively. The multifunctional MXene/CNT based layered film prepared by a simple fabrication method that integrates hydrophobicity, dual-driven heating, and sensibility together, which shows potential application in icing detection, anti-icing, and deicing.